Comparison Between Physical Exercise and Alendronate Against Bone Calcium Levels and Body Weight In Wistar Rats Model Glucocorticoid-Induce Osteoporosis - Hanna Cakrawati; Minarma Siagian; Neng Tine Kartinah (Universitas Muhammadiyah Malang, 2022)
Glucocorticoid-induce osteoporosis (GIO) is a bone condition with osteoporosis due to taking long-term glucocorticoid drugs which is the most common cause of increasing the number of fracture cases which is a health problem. GIO is one of the most common forms of osteoporosis in men. Sodium alendronate is a biphosponate drug that is approved for prevention and management of GIO but has serious side effects on long-term use. Doing physical exercise